PERANCANGAN ULANG TURBIN KAPLAN POROS VERTIKAL DI PLTM PLUMBUNGAN - Saputra, Rudi; Liichan, Taff (Bina Teknika, 2018)
Hydroelectric Power Plants (PLTA) in Indonesia have been around since 1926, and are still operating today. The Indonesian government represented by PT. PLN (State Electricity Company) will continue to maintain, operate and maintain old hydropower plants. So far, the development and development of PLTMH in Indonesia still uses consultants / contractors and its manufacturing is from overseas, even components (spare parts) are also still dependent on the technology producers themselves, the majority of which are foreign countries. Imports cannot be avoided, this results in us being vulnerable to several things, fluctuations in foreign exchange rates, and dependence on foreign producers. But with the increasing understanding of national resilience, especially in terms of national industrial independence, several national companies began to carry out reconstruction and fabrication for hydroelectric power plants. This is encouraging the author to learn to know, understand, how to plan the main parts of the Kaplan Turbine which include: runner, shaft, spiral casing, stacker, draft tube. In this plan the author focuses on calculating the main dimensions of the Kaplan Turbine. From the results of the design and calculation, the appropriate type of turbine is Kaplan Turbine as an electric generator drive in Plumbungan PLTM with installed power of 1.2 MW, maximum head of 21.16 meters and water discharge requirement of 7.68 m3 / sec. Plumbungan PLTM installation consists of turbines, turbine supporting equipment, and turbine operation aids. The turbine installation component consists of: suction pipe (penstock), turbine house (spiral casing), runner, runner shaft, shaft support bearing and draft tube.